2018
DOI: 10.1074/jbc.ra117.001213
|View full text |Cite
|
Sign up to set email alerts
|

A trapped human PPM1A–phosphopeptide complex reveals structural features critical for regulation of PPM protein phosphatase activity

Abstract: Metal-dependent protein phosphatases (PPM) are evolutionarily unrelated to other serine/threonine protein phosphatases and are characterized by their requirement for supplementation with millimolar concentrations of Mg 2+ or Mn 2+ ions for activity in vitro. The crystal structure of human PPM1A (also known as PP2Cα), the first PPM structure determined, displays two tightly bound Mn 2+ ions in the active site and a small subdomain, termed the Flap, located adjacent to the active site. Some recent crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…A recent study reported the crystal structure of a "substrate trapped" catalytically inactive mutant of PPM1A complexed with a phosphorylated peptide substrate [36]. This substrate trapping conformation was achieved by mutation of an Asp residue (Asp146 in PPM1A) that is conserved in 16 out of 20 PPM family phosphatases.…”
Section: Identification Of a Substrate Trapping Ppm1h Mutantmentioning
confidence: 99%
“…A recent study reported the crystal structure of a "substrate trapped" catalytically inactive mutant of PPM1A complexed with a phosphorylated peptide substrate [36]. This substrate trapping conformation was achieved by mutation of an Asp residue (Asp146 in PPM1A) that is conserved in 16 out of 20 PPM family phosphatases.…”
Section: Identification Of a Substrate Trapping Ppm1h Mutantmentioning
confidence: 99%
“…; Debnath et al . ). Studies have shown loss of M3 binding has no effect on the binding of the first metal (M1) and the second metal (M2) in the catalytic center but notably impaired the catalytic activity in Thermosynechococcus elongatus and necessity of M3 in PPM‐catalyzed reactions (Su et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Debnath et al . ). By determination of the PPM1K‐N94K crystal structure, we identified that the PPM1K‐N94K mutant accommodates a third Mg 2+ in the active site, accompanied with the slight change in the coordination state of two known conserved metal ion (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…The method allows to introduce N,N-dialkyldiamide-type phosphate protecting group, which can be easily converted into the corresponding phosphate under mild conditions (method A: 2M HCl/ dioxane = 1/1 in 6 h; 69 method B: 0.04 M HCl (pH 2) in 36 h). 70 This approach was successfully employed in the synthesis of a spy molecule for 19 F NMR displacement assays to study pY-peptides binding to SOCS2, 14 as well as to obtain inhibitors of STAT3 protein (Fig. 5A).…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…[9][10][11][12][13] Such compounds can also provide useful tools for biophysical protein characterization, 14 for monitoring enzyme activity, 15,16 and as antigens for raising antibodies. 17,18 Moreover, synthetic pYcontaining peptides have been used to obtain co-crystal structures of protein-peptide complexes, 11,14,19,20 revealing structural insights into substrate recognition and specificity of the enzymes, and guiding structure-based drug design. Additionally, the immobilisation of pY on agarose gel has allowed the purification of human immunoglobulin G (IgG) 21 and pre-miRNA (MicroRNA)-29 (ref.…”
Section: Introductionmentioning
confidence: 99%